Key Factors Shaping Undergraduate Attitudes and Purchase Intentions for Live-Stream Shopping: A Study in Mianyang, China - Hu, Jiemei (Scholar: Human Sciences, 2025)
Purpose: This paper aims to study the factors influencing the Live-stream Shopping Cognitive attitudes and purchase intentions of undergraduate students in Mianyang. The conceptual framework demonstrates the causal relationships between customer engagement, professionalism, interaction, price discount, cognitive trust, perceived risk, perceived satisfaction, and purchase intention. Research design, data, and methodology: The researchers employed quantitative techniques (n=500) to distribute questionnaires to undergraduate students from four majors—Biological Engineering, Architectural Engineering, Information Engineering, and Environmental Engineering—at Southwest University of Science and Technology in Mianyang, Sichuan Province, China. Non-probability sampling methods were used, including judgment sampling to select the four majors, quota sampling to determine the sample size, and convenience sampling to collect data and distribute questionnaires both online and offline. The researchers used Structural Equation Modeling (SEM) and Confirmatory Factor Analysis (CFA) for data analysis, which included model fit, reliability, and construct validity. Results: The results indicate that customer engagement, professionalism, interaction, and price discounts significantly affect purchase intention. Cognitive trust and perceived risk significantly influence perceived satisfaction, which has a significant impact on purchase intention. Conclusions: These findings have significant implications for the field of marketing and e-commerce. Therefore, we suggest that in order to create a better and more stable shopping environment for undergraduate students, and to stabilize consumption within this group, livestreaming platforms should consider implementing specific strategies.